Investigation of biodiesel fuel properties with the dispersion of carbon nanotubes - Dinish, Thegaraju (2012)
This project reports on the use of carbon nanotubes as additive.to the biodiesel fuel and its effects to the operational characteristics of the fuel The objective of this project is to investigate the properties of palm oil biodiesel dispersed with carbon nanotubes in order to achieve improved operational characteristics and performance. In this study, the tested fuels were prepared by dispersing CNT into the fuels at five different concentrations of 0.5 % vol, 1.0 % vol, 1.5 % vol, 2.0 % vol, 2.5 % vol and have their properties tested and be compared against standard fuels. Experimental results have shown that the thermal conductivities and flash points of the fuels dispersed with CNT have increased with higher concentration of CNT. The pour point data have shown decremental values when dispersed with CNT at higher concentrations and the dispersion of CNT has increased the cetane number and higher heating value of the fuels. As a conclusion, dispersion of CNT as additive has improved the properties and the operational characteristics of biodiesel fuel and its blends.